1969
DOI: 10.1002/1097-0142(196906)23:6<1332::aid-cncr2820230615>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Primary carcinoma of the fallopian tube

Abstract: Among patients with cancer of the uterine adnexa in the 3 Danish Radium Centres, 38 were found to have tubal cancer. The diagnosis is difficult; the most important factor in early recognition is to bear in mind the possibility of tubal cancer when dealing with patients in the high‐incidence age group. During recent years, the incidence of the disease has been increasing. Age distribution, the side affected, and sterility were in accordance with previous findings. The prognosis depends more upon the clinical de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1
5

Year Published

1970
1970
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
1
8
1
5
Order By: Relevance
“…The reproducible SV40 transformation of human epithelial amnion cells in vitro and the characteristics of the strains of transformed cells during subcultivation, have been reported previously (1)(2)(3)(4). Since we have established that mycoplasma infection may affect spontaneously transformed amnion cells of the FL line, causing changes in morphology and growth ( 5 ) , in chromosome numbers and abnormalities (6)(7)(8), 2nd in tumor-producing capacity (9), it seemed pertinent to investigate possible effects of mycoplasma on SV40 transformation of amnion cells.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…The reproducible SV40 transformation of human epithelial amnion cells in vitro and the characteristics of the strains of transformed cells during subcultivation, have been reported previously (1)(2)(3)(4). Since we have established that mycoplasma infection may affect spontaneously transformed amnion cells of the FL line, causing changes in morphology and growth ( 5 ) , in chromosome numbers and abnormalities (6)(7)(8), 2nd in tumor-producing capacity (9), it seemed pertinent to investigate possible effects of mycoplasma on SV40 transformation of amnion cells.…”
supporting
confidence: 59%
“…were considerably reduced ( 1 : 2 or 1 : 3 ) compared to SV40 transformed amnion strains in general (2,4,13). A most unusual SV40 production picture was observed.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…It has been reported that a reduction in the malignancy of cells followed a mycoplasma infection that was cured (22). Another reported effect of mycoplasma was to increase dramatically the cloning efficiency of BHK21/C13 hamster cells in agar (23).…”
Section: Resultsmentioning
confidence: 99%